2019
DOI: 10.1007/s10549-018-05125-4
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib plus letrozole as first-line therapy in estrogen receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer with extended follow-up

Abstract: Purpose In the initial PALOMA-2 (NCT01740427) analysis with median follow-up of 23 months, palbociclib plus letrozole significantly prolonged progression-free survival (PFS) in women with estrogen receptor-positive (ER+)/human epidermal growth factor receptor 2-negative (HER2−) advanced breast cancer (ABC) [hazard ratio (HR) 0.58; P < 0.001]. Herein, we report results overall and by subgroups with extended follow-up. Methods In this double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
282
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(342 citation statements)
references
References 17 publications
(20 reference statements)
27
282
3
10
Order By: Relevance
“…Endocrine therapy and CDK 4/6 inhibitor combinations have substantially prolonged progression-free survival making them a standard of care for advanced luminal breast cancer. [2][3][4][5][6][7][8] Increased transaminases have been described as adverse events in previous phase 3 trials (Table 1).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Endocrine therapy and CDK 4/6 inhibitor combinations have substantially prolonged progression-free survival making them a standard of care for advanced luminal breast cancer. [2][3][4][5][6][7][8] Increased transaminases have been described as adverse events in previous phase 3 trials (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…Here, for the first time, we report the case of a rechallenge of a CDK 4/6 inhibitor after serious liver toxicity. Endocrine therapy and CDK 4/6 inhibitor combinations have substantially prolonged progression‐free survival making them a standard of care for advanced luminal breast cancer . Increased transaminases have been described as adverse events in previous phase 3 trials (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PALOMA‐2 and PALOMA‐3 trials, palbociclib plus ET prolonged PFS in the North American and overall populations (median PFS in PALOMA‐2: 25.4 and 27.6 months, respectively; PALOMA‐3: 9.9 and 11.2 months, respectively) and delayed treatment with cytotoxic chemotherapy. Updated data for North American patients from the PALOMA‐3 trial also indicated that OS was longer with palbociclib vs placebo (32.0 vs 24.7 months, HR, 0.75 [95% CI, 0.53–1.04]), P = .0869]), similar to results seen in the overall population (34.9 vs 28.0 months, HR, 0.81 [95% CI, 0.64–1.03]), P = .09]) …”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib (125 mg, 28-day cycle with aromatase inhibitor) is used as the targeted therapy against ER + /HER2 − advanced and metastatic breast cancer in conjunction with hormone therapy. The open label PALOMA (Palbociclib: Ongoing Trials in the Management of Breast Cancer) clinical trials were designed recently with either aromatase inhibitor (letrozole) (PALOMA-1 or PALOMA-2 Trials) [111,112] or Fulvestrant hormone therapies (PALOMA-3 trails) [113]. An improvement in the overall survival of metastatic breast cancer patients was reported in PALOMA-3 phase III clinical trials.…”
Section: Cdk4/6 Inhibitormentioning
confidence: 99%